Moralitas Digital Refleksi atas Nilai-nilai Al-Qur'an dalam penggunaan Teknologi - akib, mohammad (Sekolah Tinggi Ilmu Tarbiyah Al - Ibrohimy Bangkalan, 2024)
This article reviews the concept of digital morality as a reflection of the values ​​contained in the Koran in the context of the use of technology. By considering the challenges and opportunities facing Muslims in the digital era, this article explores how the teachings of the Qur'an can guide individuals in using technology responsibly and ethically. Discussions cover moral aspects such as integrity, privacy, tolerance and justice in the use of digital technology, as well as efforts to apply Al-Qur'an principles in the online environment. Through this analysis, this article aims to provide a better understanding of the importance of digital morality in the Islamic context and how the values ​​of the Qur'an can guide Muslims' online behavior.